Financial performance analysis of Regional Government - Nur Rachma; Dara Ayu Nianty; Un Dini Imran (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
This study uses secondary figures, i.e., reports from the Directorate General of Fiscal Balance and the Supreme Audit Agency on implementing the District Government and the Government of the Majene Regency in 2018 and 2019. This study shows that (1) the financial performance of the Regional Government of Majene Regency, as shown in the Regional Budget for 2019 by the analysis of variances, is well established. (2) the 2019 ABPD level of efficiency and efficiency is less efficient in the Majene Regency. It can be said that Majene Regency's level of financial achievement is less efficient. On efficiency, the level of achievement of Majene Regency's regional financial performance is beneficial. (3) the independence story remains shallow in 2018 and 2019.